Pengelompokan Penyakit Pada Pasien Berdasarkan Usia Dengan Metode K-Means Clustering (Studi Kasus : Puskesmas Bahorok) - Tanty Tanty; Budi Serasi Ginting; Magdalena Simanjuntak (UIN Sumatera Utara, 2021)
In this study, the process of applying the K-Means method will be carried out in classifying diseases in bahorok health center patients based on age. To simplify the process of managing a lot of data, the Bahorok Health Center needs a system in making decisions to find out the grouping of diseases based on the age of patients who are often affected by the disease at the Bahorok Health Center. The application of the K-Means Clustering method is a method used in data mining which works by finding and classifying data that have similar characteristics between one data and other data that has been obtained. As for the results. The results of the pattern analysis above From 20 data obtained 3 groups, it can be concluded as follows: Group 1 Centroid 1: (2.2 1.4 2.2) there are 5 data. Based on the above calculations, it can be seen that in cluster 1 group 1, the patients are children. Group 2 Centroid 2: (1 1,6 1,6) there are 3 data. Based on the above calculations, it can be concluded that in cluster 2, group 2 is an adult patient. Group 3 Centroid 3: (1,75 1,58 6) there are 12 data. Based on the above calculations, it can be concluded that in cluster 3, group 3 is the patient is the elderly. Keywords : K-Means, Diseases in Patients